2022
DOI: 10.31234/osf.io/epnvs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Longitudinal Study on Cognitive Aging in Autism

Abstract: Background: Longitudinal studies on cognitive aging in autism are scarce, and largely underpowered, yet essential to obtain more conclusive results on cognitive changes in autism during adulthood. In this large-scale longitudinal study, age-related changes in autism were investigated in a wide range of cognitive abilities. Methods: As pre-registered, we used reliable change indices and multilevel models to estimate cognitive changes in a sample of 128 autistic, and 112 non-autistic adults (age range: 24-85 yrs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…At least in a recognition format, autism, and older age result in less differences in cognitive strategy use than previously expected. Furthermore, consistent with our earlier work (Torenvliet et al, 2021(Torenvliet et al, , 2023 we demonstrated parallel age-related effects between those with-and without autism, reducing the likelihood of both accelerated, and protective age-related patterns in autism.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…At least in a recognition format, autism, and older age result in less differences in cognitive strategy use than previously expected. Furthermore, consistent with our earlier work (Torenvliet et al, 2021(Torenvliet et al, , 2023 we demonstrated parallel age-related effects between those with-and without autism, reducing the likelihood of both accelerated, and protective age-related patterns in autism.…”
Section: Discussionsupporting
confidence: 92%
“…Age-related differences in autistic and non-autistic people were similar, with significantly slower, and less accurate responses in older, compared to younger individuals. This is consistent with our previous observations of parallel cross-sectional and longitudinal age-related effects in autism (Torenvliet et al, 2021(Torenvliet et al, , 2023. Hence, based on these results visual memory performance and objective strategy use seems similar in autistic-and nonautistic adults, with parallel age-related patterns.…”
Section: Equal Memory Performance and Strategy Use In Autismsupporting
confidence: 92%
See 2 more Smart Citations
“…In the past decade, the literature on cognitive aging in autistic people has developed rapidly. Most crosssectional studies seem to observe similar age-related effects (i.e., parallel aging) between autistic-and nonautistic adults (Lever & Geurts, 2016;Torenvliet et al, 2021;Tse et al, 2019), yet others have observed evidence for increased age-related effects (i.e., accelerated aging) at least in some domains (Abbott et al, 2018;Baxter et al, 2019;Geurts & Vissers, 2012;Powell et al, 2017). Moreover, advantageous age-related effects have also been observed in which older autistic individuals seemed less prone to age-related effects (i.e., protective aging; Lever et al, 2015;Zivrali Yarar et al, 2020).…”
mentioning
confidence: 99%